A aprendizagem de libras e de português em contexto de tandem: um estudo com alunos do curso de Letras: Libras da UFG - Oliveira, Quintino Martins de (2017)
This study focuses on the collaborative learning between two deaf and two hearing students who take Libras as a major at Universidade Federal de Goiás. They had to teach their language to each other in a tandem collaborative learning processes. The study took place on the first term of 2017. Tandem learning is a process of cultural and linguistic exchanges among individuals who have different languages and are willing to teach each other their language in a collaborative way. Thus, the deaf participant taught Libras to the hearing peer and learned written Portuguese from him/her. This study also aims to investigate if collaboration in tandem context can favor the learning of Libras and Portuguese, since they are languages that have different linguistic modalities. It also investigates which strategies were taken by the participants to teach each other´s language and the perceptions they had about the collaborative learning process in tandem context. It is a qualitative case study whose data were collected through the video recording of the interactions and the interviews. Data analysis shows that the students used some strategies that mediated the learning process, such as the use of realia, the use of images, etc. The results also show that the interactions favored not only linguistic knowledge, but also cultural exchanges and that the deaf students ought to be taught by the use of sign language. This study aims to bring some reflections on the learning process in tandem context when the languages involved have different linguistic modalities, as well as bring some guidance to future language teachers who might teach those languages in similar contexts.